Mitigating blind spot collision utilizing ultrasonic gap perimeter sensor - Md Esa, Muhamad Matta (2013)
Failure to identify the vehicle by the side of the vehicle or in other word as blind spot area, especially larger vehicles are one of the causes of the accident. For some drivers, the simple solution is to place an additional side mirror. However, it is not the best solution because this additional side mirrors do not provide an accurate picture of actual or estimated distance to the object or another vehicle. The objective of this project is to identify the causes of automobile collisions, notably the side collision impact causes by the blind spot, to develop a system that can detect the presence vehicles on the side and to develop a system that are affordable for normal car users. To achieve this objective, flow chart was designed to help write coding using Arduino 1.0.2 and design hardware. This system can detect the obstacle within range 2cm to 320cm from the edge of the project vehicle. Before this system developed, the survey was conducted to determine what the driver wants. After that, the design process is carried out. The input to this system is Ping ultrasonic sensor, LCD, LED, and siren for the output part. LCD and LED were displaying the distance from the vehicle and the siren will be switched on to warn the driver when have obstacle in the blind spot area. As a conclusion, the Mitigating Blind Spot Collision Utilizing Ultrasonic Gap Perimeter Sensor System has successfully completed. This system able to detect the presence of other vehicles on the side of the project vehicle, especially in the blind spot area and will alert the driver when the vehicle is nearby when the alarm system is operated. The efficiency of this system to detect objects in the blind spot area is 79.82%. Others, it will give the display value less than one second after obstacle exists in front of the sensor. This operating time is most important because if the system is slow, the main function of this system to detect the obstacle in the blind spot area is not achieved.